Pension reforms in Central, Eastern, and Southeastern Europe from post-Socialist transition to the global financial crisis - Guardiancich, Igor, 1976- (Routledge/EUI studies in the political economy of welfare ;, 2013)
"This book traces and analyzes the legislation and implementation of pension reforms in four Central, Eastern and Southeastern European countries: Croatia, Hungary, Poland and Slovenia. By comparing the political economy of their policymaking processes, it seeks to pinpoint regularities between institutional settings, actor constellations, decision-making strategies and reform.Guardiancich employs a historical institutionalist framework to analyze the policies, actors and institutions that characterized the period between the collapse of socialism and the global financial crisis of 2008-2009. He argues that viable pension reforms should not be seen simply as an event, but rather as a continuing process that must be fiscally, socially and politically sustainable. In particular, the primary goal of a pension scheme is to reduce poverty, provide adequate retirement income and insure against the risks of old age within given fiscal constraints, and this will happen only if the scheme enjoys continuing political support at all levels.This book will be of interest to students and scholars of political science, political economy, social policy and economics"--